Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.bpj.2010.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Control of Ca2+ Release by Action Potential Configuration in Normal and Failing Murine Cardiomyocytes

Abstract: Cardiomyocytes from failing hearts exhibit spatially nonuniform or dyssynchronous sarcoplasmic reticulum (SR) Ca(2+) release. We investigated the contribution of action potential (AP) prolongation in mice with congestive heart failure (CHF) after myocardial infarction. AP recordings from CHF and control myocytes were included in a computational model of the dyad, which predicted more dyssynchronous ryanodine receptor opening during stimulation with the CHF AP. This prediction was confirmed in cardiomyocyte exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…2, C ii), implying that the relative position of the molecules is not determined by chance. Modeling has demonstrated that the relative position of the molecules impacts the gain of ECC (19,20), so grouping Ca 2þ channels together near the center of the RyR cluster should increase the probability that the released Ca 2þ ions will bind with a RyR, ensuring that the couplon is activated. Finally, these results disagree with freeze-fracture analyses suggesting that the molecules occupy roughly the same area in their respective membranes and that Ca v 1.2 is randomly positioned relative to RyR (18).…”
Section: Discussionmentioning
confidence: 99%
“…2, C ii), implying that the relative position of the molecules is not determined by chance. Modeling has demonstrated that the relative position of the molecules impacts the gain of ECC (19,20), so grouping Ca 2þ channels together near the center of the RyR cluster should increase the probability that the released Ca 2þ ions will bind with a RyR, ensuring that the couplon is activated. Finally, these results disagree with freeze-fracture analyses suggesting that the molecules occupy roughly the same area in their respective membranes and that Ca v 1.2 is randomly positioned relative to RyR (18).…”
Section: Discussionmentioning
confidence: 99%
“…20–30 minutes before the anesthetization [3, 1113] to prevent blood clotting and possible myocardial infarction. Animals are anesthetized using either injectable (pentobarbital, ketamine/xylazyne) or inhalable (isoflurane) anesthetics [3, 13, 14]. It has been reported that the use of inhalable anesthetics for small animals such as mice and rats avoids the risk of myocardial ischemia since the onset of anesthesia is rapid with minimal effects on respiration [15].…”
Section: Cardiomyocyte Isolationmentioning
confidence: 99%
“…A large number of animal (He et al 2001;Benitah et al 2002;Balijepalli et al 2003;Louch et al 2010a) and human (Lyon et al 2009;Crossman et al 2011) studies have demonstrated that one of the principal insults to local CICR in HF is loss of the t-tubules. These regular membrane invaginations relay the action potential to the depth of the cell rapidly, facilitating synchronous Ca 2+ release from the entire cell (Orchard & Brette, 2008).…”
Section: Introductionmentioning
confidence: 99%